Volume 1: Processing 2015
DOI: 10.1115/msec2015-9261
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Corrosion Resistance of AISI H13 Steel Machined by Electro Discharge Machining

Abstract: Electro discharge machining (EDM) technique is widely used in the die and mold industries for its distinct advantages in machining hard metals. Nevertheless, the properties of EDM treated steel, especially its corrosion resistance, have not been well understood or clearly identified. In this paper, electrochemical corrosion behavior of EDM treated AISI H13 steel in NaOH solution was investigated, with the diamond polished being reference specimen. The corrosion resistance of the specimens was evaluated by elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…So, the local temperature can increase to more than 10000 °C at the micro-second time intervals. 3,4 Hence, the temperature gradient developed on the surface of the workpiece leads to melting and changing material constituents, 5 as well as diffusion of very small particles to the surface of the tool electrode 6 , and Hence changing the mechanical, 7,8 structural 9 and electrochemical 10 properties of the workpiece. These alterations are related to machining parameters such as electrical discharge current (I), the type of modulation of applying voltage (V), the time in which modulated voltage has been pulse-on time (t on ) and pulse-off time (t off ), machining time (τ), and the type of tool electrode and work-piece.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, the local temperature can increase to more than 10000 °C at the micro-second time intervals. 3,4 Hence, the temperature gradient developed on the surface of the workpiece leads to melting and changing material constituents, 5 as well as diffusion of very small particles to the surface of the tool electrode 6 , and Hence changing the mechanical, 7,8 structural 9 and electrochemical 10 properties of the workpiece. These alterations are related to machining parameters such as electrical discharge current (I), the type of modulation of applying voltage (V), the time in which modulated voltage has been pulse-on time (t on ) and pulse-off time (t off ), machining time (τ), and the type of tool electrode and work-piece.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have evaluated the Karimi et al: Study of Electrical Discharge Machining Parameters on ... corrosion behavior of the workpieces made by EDM showing the tool electrodes significantly affect the amount of workpiece corrosion. 6,10,15,[21][22][23][24] Yan et al using weight loss test have shown that Al-Zn-Mg alloy machined by a copper electrode has high corrosion resistance. 21 Tsai et al have developed a sintered electrode tool made in Cu-Cr (80-20%) composite to improve the uniform corrosion resistance of the AISI 1045 EDM surfaces.…”
Section: Introductionmentioning
confidence: 99%